Kajian Strategi Produksi Bersih Pada Industri Pati Sagu Skala Medium: Studi Kasus Di Cimahpar Kecamatan Bogor Utara - Mega Ayu Yusuf; Muhammad Romli (Musamus AE Featuring Journal, 2020)
Medium scale industries are gaining importance and their contribution to pollution problems cannot be ignored. One of medium scale industry having the potential to cause environment problems is centralized of medium scale sago starch industries. Medium scale industries typically have limited space for the installation of treatment system. In addition, often medium scale industries are only marginally profitable, so waste treatment investment may threaten their viability. This problem can be solved by applying cleaner production strategy. This research studies the potentials of cleaner production application and formulating alternatives of cleaner production strategy in order to develop centralized medium scale sago starch industry in Cimahpar. The cleaner production alternatives which are potential to be applied are good housekeeping, washing of sedimentation tank daily, water controling, and worker supervision. The investment of these alternatives is Rp 15 270 000 and pay back period (PBP) one year and two months. Analytical Hierarchy Process (AHP) analysis shows that technology is the most important factor to maximize sago starch production efficiency by applying cleaner production. The priority of cleaner production program from AHP analysis is socialization and training of cleaner production application, integrated waste management, and socialization and training of sago starch quality increasing procedures.